2006
DOI: 10.1097/01.hjr.0000224490.10845.26
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and gender differences in postprandial lipaemia

Abstract: Men had a more pronounced postprandial hypertriglyceridaemia and seem to have delayed TG clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 26 publications
3
24
1
4
Order By: Relevance
“…Postprandial lipemia is an independent risk factor for heart disease [4,5]. Oxidative stress and inflammation play a pivotal role in atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Postprandial lipemia is an independent risk factor for heart disease [4,5]. Oxidative stress and inflammation play a pivotal role in atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial lipemia is an independent risk factor for CVD, and a prominent feature in diabetes and MetS [4,5]. Epidemiologic studies suggest that postprandial perturbations are involved in the pathogenesis of diabetic vasculopathies [4,5]. Oxidative stress may be an important mechanism by which postprandial lipemia alters vascular function [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, 75% of women used oral contraceptives, which are known to influence the metabolic measurements. Previous studies have shown that women have lower postprandial TG levels [14], probably because of the presence of oestrogens and progestagens [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%